The Role of Stakeholders in the Management of Jurang Jero Nature Tourism Object in Mount Merapi National Park, Central Java, Indonesia - Sutata, Daris Fahmaa; Sadono, Ronggo; Marhaento, Hero (Jurnal Manajemen Hutan Tropika, 2023)
National parks, as an ecosystem protection function, are also encouraged to support local economic development. Meanwhile, community-based tourism (CBT) in the utilization zone is identified as a viable strategy to improve livelihoods for local communities and support the conservation of the national park. This research aimed to identify stakeholders and their roles in the management of the Jurang Jero Nature Tourism Object (JJNTO) in Mount Merapi National Park (MMNP). There were 16 existing stakeholders, including government officials, community members, and the private sector, from the two villages adjacent to JJNTO, who were interviewed using an open-ended interview guide. The data were analyzed using social network analysis (SNA) with the software NodeXL Basic, followed by network visualization with Kumu.io software. The results showed that the strength and closeness of the relationship among all stakeholders were at a moderate level, approaching 57% of network density. Centrality analyses identified the Head of Jurang Jero Tourism Group, the Head of Randu Ijo Forest Farmer Group, and the Head of Srumbung Resort as the three most important stakeholders. Therefore, the role of all stakeholders still needs to be improved to support the management of CBT and MMNP conservation efforts, specifically from the private sector, the environment, and tourism agencies, by improving communication and joint commitments to create cooperation and partnerships.